Bariatric Surgery in Clinical Practice (Springer Nature, 2022)
obesity; disease; bariatric surgery; clinical practice
English
Keywords: obesity; disease; bariatric surgery; clinical practice; thema EDItEUR::M Medicine and Nursing::MJ Clinical and internal medicine::MJC Diseases and disorders